Life Skills and Literary Texts about the First World War - Torunn Synnøve Skjærstad (CLELEjournal, 2024)
This report describes a study conducted in a 9th grade English class, which addresses how literary texts about the First World War opened spaces for the life skills of critical thinking and empathy in an English language classroom in a lower secondary school in Norway.